QTL Mapping of Pericarp Thickness in Immature and Mature Stages in Thai Tropical Sweet Corn (Zea mays var. saccharata) - Kitti Wanlayaporn (Science Faculty of Chiang Mai University, 2019)
Sweet corn (Zea mays var. saccharata) is one of the most important crop species in Thailand. It is consumed fresh and as processed food. Pericarp thickness of sweet corn seed is a characteristic that directly affects consumers’ taste satisfaction. Here, we used pericarp weight as a proxy for pericarp thickness to identify the quantitative trait loci (QTL) controlling pericarp thickness of Thai sweet corn in 109 recombinant inbred lines (RILs) derived from a cross between hA9104 (thicker pericarp) and hA9035 (thinner pericarp). We obtained a linkage map consisting of 162 simple sequence repeat (SSR) markers, distributed over 10 linkage groups. The genetic map spanned the length of 2693.8 cM with an average distance between markers of 16.62 cM. Eleven QTLs regulating pericarp weight in both immature and mature stages were found on linkage groups 1, 2, 4, 5, 9 and 10. Phenotypic variance (PVE) of each QTL ranged from 0.3% to 73.6%.The major QTL was detected on linkage group 5, flanked by markers bnlg278 and phi128. The large proportion PVE of the QTL was 73% for immature and 41% for mature stages. Information gained about the QTL loci responsible for pericarp thickness in sweet corn provides a specific genetic region used for the development of gene-based markers, which would be useful for marker assisted selection for pericarp thickness improvement in corn in the future.